Écologie microbienne en milieu aquatique : des virus aux protozoaires - Amblard, C.; Boisson, J. C.; Bourdier, G.; Fontvieille, D.; Gayte, X.; Sime-Ngando, T. (Revue des sciences de l'eau, 1998)
Par leur abondance et leur diversité taxonomique et fonctionnelle, les microorganismes jouent un rôle prépondérant dans les flux de matière et d'énergie au sein des écosystèmes aquatiques.Au cours de ces dernières années, les progrès réalisés au niveau des techniques d'identification, de dénombrement et de mesure d'activité métabolique, notamment en microscopie à épifluorescence et en biologie moléculaire, ont permis d'entrevoir l'extraordinaire diversité des microorganismes aquatiques, l'étendue de leurs conditions de vie et leurs abondances jusqu'alors largement sous-estimées. De plus, l'amélioration sensible des méthodes séparatives a permis de décrire, in situ, la composition biochimique des communautés et d'aborder les transferts de matière sous un angle qualitatif.L'ensemble des résultats disponibles laisse apparaître que les relations trophiques entre les microorganismes forment un véritable réseau à l'intérieur duquel la boucle microbienne permet le transfert, au moins en partie, de la production picoplanctonique vers les niveaux trophiques supérieurs. Ainsi, des progrès conséquents ont été réalisés quant à la compréhension du rôle des communautés bactériennes dans les flux de matière, y compris au niveau d'environnements particuliers (biofilms, milieux extrêmes). Par ailleurs, alors qu'il a été longtemps admis que la régulation des communautés bactériennes était essentiellement liée à la disponibilité ou à la qualité des substrats organiques, il apparaît maintenant que la limitation par les éléments nutritifs minéraux, la prédation des protistes phagotrophes et du métazooplancton et la lyse virale sont également des facteurs susceptibles d'intervenir significativement dans ce contrôle.Malgré ces progrès considérables dans le domaine de l'écologie microbienne, près de 90% des microorganismes présents dans l'environnement n'ont pas encore été décrits et la compréhension des relations entre les microorganismes et le fonctionnement des écosystèmes restent un enjeu majeur pour les années à venir. Recent advancements in the ecology of aquatic microbial communities, i.e. from viruses to protozoa, are summarized in this paper. The abundance and both taxonomic and functional diversities of microorganisms in the sea and in inland waters indicate that microbes play a key role in nutrient cycling and energy flows in aquatic ecosystems. In recent years, aquatic microbiology has indeed undergone profound changes due to the improvement of methods for identifying, counting, and essaying biochemical composition and metabolic activities of aquatic microbial assemblages. Specifically, the impact of new developments in microscopy (e.g. epifluorescence, immunofluorescence.) and in cell and molecular biology has allowed to realize that microbes are omnipresent in aquatic systems (including extreme environments such as Arctic, Antarctic, Deep ocean, Hydrothermal vents.). Derived from direct counting under epifluorescence microscope that is able to visualize cellular pigment autofluorescence, recent total numbers of pelagic microbes generally vary from 105 and 102 cells ml-1 in oligotrophic systems, to 107 and 105 cells ml-1 in productive waters, for heterotrophic bacteria and heterotrophic flagellated protists, respectively. These bacterial numbers are significantly higher than previous estimates, derived from the indirect method of growing bacterial cells in selective culture medium. The use of adequate fixatives has allowed the counting of ciliated protozooplankton (range: < 1 - 50 cells ml-1) under inverted microscope. The use of artificial or natural fluorescent tracers now allows, via direct microscopic observation of protistan digestive vacuoles or the alimentary tract of some metazoan, the quantification of matter flows in the aquatic microbial webs. Besides, the coupling between fluorochrome dying of aquatic microbes and flow cytometric analyses allows to measure the cell size and abundance of the tiniest planktonic single-celled organisms, and to characterize some cellular constituents (e.g. ADN, protein.) or functions (e.g. membrane potential, enzymatic activity.). Other methodological improvements of the identification, counting, and essaying the biochemical composition of aquatic microorganisms come (1) from the separative chromatography that allows to describe the in situ biochemical composition of microbial communities, and to have access to a qualitative measurement of matter flows within aquatic microbial compartments, and (2) from the use of rRNA-targeted oligonucleotide probes that allows, after amplification by the polymerase chain reaction, to detect and quantify individual species in natural assemblages of microbial organisms (i.e. bacterio- and protoplankton). Concerning the assessment of metabolic activity, a method based on short-term incubations of water samples in the presence of radiolabeled compounds, primarily 3H-thymidine and 3H-leucine, has been widely developed and used during the few past years, to measure bacterial production in aquatic systems.In the light of the above recent methodological improvements, it appears that aquatic microbial communities form complex food webs in which heterotrophic bacteria play a key role. These organisms decompose particulate matter or polymeric dissolved compounds, and rapidly utilize simple organic molecules. However, depending on their qualitative characteristics, some of these simple dissolved substrates can accumulated during certain times or in some aquatic environments. This has been relied to several hypothesis, including the higher diversity of natural organic molecules compared to the bacterial enzymatic pool, chemical constraints during microbial incorporation of substrates, and the fact that organic molecules can become refractory before utilization by ambient bacteria. Because bacterial metabolic efficiencies can vary widely both intra- and interspecifically, it is propose that the ecology of aquatic bacteria should gain in substance if considering functional groups (separated by criteria such as energy sources, .) rather than taxonomic groups.The seasonal abundances of pelagic bacteria are regulated by several factors, including temperature, resources, and predation. The general significant correlation between bacterial and primary production in both fresh- and marine waters suggests that organic substrates from algal exudation regulate bacterial communities. However, uncoupling between bacterial and algal production has been reported for some aquatic environments and during some times. It is now well known that bacteria and phytoplankton can compete for the same substrate source (including mineral nutrients). The accumulation of biodegradable dissolved organic carbon (DOC) in the euphotic zone of oligotrophic marine systems imply that factors other than substrate availability can regulate bacterial production. For example, in situ and experimental studies have recently demonstrated that mineral phosphorus (PO4) can limit bacterial growth in lakes where both autochtonous and allochtonous DOC are prevalent. Limitation of bacteria by mineral P and N has also been reported in marine systems. Besides, the relatively constant ratio between bacterial and phagotrophic flagellate abundances in pelagic fresh- and marine waters has been interpreted as the result of the impact of bacterivorous protist (mainly represented by flagellated protists) activity on bacterioplankton seasonal abundance. Both in situ and experimental essays have indeed shown that a flagellate can ingest from 10 to 250 bacteria hour-1. Protozooplankton bacterivory is actually considered the root of a system, i.e. the microbial loop (dissolved organic matter --> bacteria --> protozoa.), that can act as a significant mediator of energy transfer to the upper trophic levels, by recovering part of the primary production that would otherwise be lost from the system. Part of protistan grazing activity is from mixotrophic protists whose, in some lakes and during certain seasons, can dominate the total bacterivory. In general, predator-prey interactions among protists are as complex as those among metazoa, and chemical communications may operate as well as behavioral and polymorphic adaptations.Even though the contribution of water ecosystems for disseminating enteric viral pathogens has been known for decades, the importance of wild virions in structuring aquatic communities and food webs has only come to light relatively recently. Evidences of viral infections in both pro.- and eukaryotic phytoplankton, as well as in heterotrophic bacterio.- and protozooplankton, have recently brought marine biologists to question the impact of viroplankton on processes such as 1.the mortality of microorganisms, 2. the nutrition of heterotrophic protists, 3. the promotion of genetic material exchanges among microbial populations, 4. the maintenance of species diversity, 5. the induction of planktonic aggregates, and 6. the cycling of organic matter in aquatic ecosystems. Viruses undoubtedly influence to various degrees the biological processes in aquatic ecosystems, although almost all studies on the ecology of pelagic viruses are done during a limited period of year, mainly in marine waters situated in temperate zones.Finally, despite the manifest significance of new findings in the field of aquatic microbial ecology, about 90% of microorganisms present in the environment have not yet been described. Therefore, the understanding of the interactions within microbial communities in relation to the functional dynamics of ecosystems remains of major interest for the future. We conclude that this task is to be include on the agenda of both marine and freshwater biologists as a high priority concern for the near future, partly because aquatic microbes constitute a major compartment for the biogeochemical cycles of elements in the biosphere.